Parental authority and management of the child’s property in the context of company shares (Discourse of Law and Administration, 2026)
The article examines the limits of exercising parental authority in managing the property of a minor child, with a particular focus on shares in limited liability companies. Parental authority encompasses the care of a child’s property, carried out with due diligence as per Articles 95 and 101-105 of the Family and Guardianship Code. This management is subject to restrictions, including the requirement to obtain court approval for actions exceeding ordinary management. Minors may acquire shares through inheritance, donation, sale, or company agreements, but their exercise by parents must align with the child’s best interests. Actions such as selling shares or voting on profit distribution resolutions exceed ordinary management and are subject to judicial oversight. The article highlights the fiduciary nature of parental authority, where parents act as legal representatives obligated to protect the child’s property interests. It underscores the need to harmonize provisions of the Family and Guardianship Code with the Commercial Companies Code, considering organizational risks in companies. It proposes amendments to the Family and Guardianship Code to introduce a catalog of actions exceeding ordinary management and expert consultation mechanisms. The study emphasizes the evolution of family autonomy in contrast to judicial intervention, incorporating ethical and economic considerations.
Keywords: parental authority; child property management; company shares; ordinary management; guardianship court